RELATIONSHIP BETWEEN THE FULFILLMENT OF SPIRITUAL NEEDS WITH THE MOTIVATION OF PATIENTS SCHIZOPHRENIA IN THE HEALTH CENTER AREA, PIDIE DISTRICT - Miniharianti Miniharianti; Badrul Zaman; Jihan Rabial (Universitas Pahlawan Tuanku Tambusai, 2023)
The fulfillment spiritual and motivational needs is very necessary for people with mental health disorders, considering that spiritual needs and motivation play an important role in changing mental status. Motivation recovery is a positive attitude, oriented towards achieving goals, namely healing and the strength that encourages individuals to recover. The purpose of this study was to determine the relationship between spiritual needs and healing motivation in schizophrenic patients. The sample in this study was 63 respondents in the Pidie Health Center area. This research used analytic method with cross sectional design. The research instrument used was a questionnaire. Data were analyzed using the chi square test. The results of the univariate analysis of the majority of respondents have spiritual in the good category (81.0%). The majority of respondents had a motivation to recover in the good category (90.1%). The results of the bivariate test showed that the p-value = 0.002 indicated that there was a relationship between fulfilling spiritual needs and the motivation to heal patients with mental disorders. This study suggests to nurses and families that it is important to meet the spiritual needs of schizophrenic patients in order to increase patient motivation and accelerate healing.